2019
DOI: 10.1038/s41598-019-50104-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of optical coherence tomography and high frequency ultrasound imaging in mice for the assessment of skin morphology and intradermal volumes

Abstract: Optical coherence tomography (OCT) and high-frequency ultrasound (HFUS), two established imaging modalities in the field of dermatology, were evaluated and compared regarding their applicability for visualization of skin tissue morphology and quantification of murine intradermal structures. The accuracy and reproducibility of both methods were assessed ex vivo and in vivo using a standardized model for intradermal volumes based on injected soft tissue fillers. OCT revealed greater detail in skin morphology, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…There may be a differentiated SC on the skin of the sole. Schuetzenberger et al claimed that it is not possible to differentiate the individual layers of the epidermis either in the skin of mice or in humans, 17 yet Sattler et al and Park (2014) believe that the first highintensity layer corresponds to the SC and may be visible in areas where it is thick (the sole area). 22,24 Sattler et al reported that the epidermis can be differentiated into two thin layers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may be a differentiated SC on the skin of the sole. Schuetzenberger et al claimed that it is not possible to differentiate the individual layers of the epidermis either in the skin of mice or in humans, 17 yet Sattler et al and Park (2014) believe that the first highintensity layer corresponds to the SC and may be visible in areas where it is thick (the sole area). 22,24 Sattler et al reported that the epidermis can be differentiated into two thin layers.…”
Section: Discussionmentioning
confidence: 99%
“…13 Information on the use of OCT in animals is rare, and most of the work on skin evaluation has been performed on humans, while only a few studies have looked at laboratory animals. [17][18][19][20] Therefore, it is important to determine whether the use of OCT for skin assessment enables both the differentiation of individual layers of the epidermis and the measurement of their thickness, about which there are conflicting views. 13,16,21,22 The aim of the present research was to evaluate the healthy skin of rats with the use of SD-OCT in order to determine whether this method will enable both the differentiation of the individual layers of the epidermis and the dermis, and the assessment of the thickness of these structures.…”
Section: Introductionmentioning
confidence: 99%
“…It offers an immediate evaluation of the HIFU treated area by obtaining high-resolution ultrasound images before and after the treatment. Previously available low-frequency (2 MHz to 6 MHz) imaging systems cannot clearly distinguish skin lesions [31][32][33], but an optimized BTB dual-mode transducer (composed of two elements that share the same housing but work independently) can provide more detailed imaging of superficial structures and irregular surfaces, including the dermis and upper layers of subcutaneous tissue in humans. Furthermore, since it is important to apply delicate and detailed procedures to subcutaneous layers during skin treatment, we increased the efficiency of the transducer by press-focusing and increasing the focal strength while reducing the aperture size of the transducer.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various imaging modalities, ultrasound (US), a combination of gray-scale and color Doppler flowing imaging (CDFI), is widely used because of its convenience and real-time observations. A US with a high-frequency transducer can observe the structure of superficial tissues in gray-scale, including skin (2,3), Original Article and it has been used to assess skin and subcutaneous tissue inflammation, tumors, and skin condition (4)(5)(6). CDFI can be used to observe blood flow; however, sensitivity is low in detecting tissue blood vessels, and it is difficult to detect low-speed blood flow signals.…”
Section: Introductionmentioning
confidence: 99%